x=chocolate bars
y=packs of gum
3x+y=1.75
2x+4y=2.00
Multiply the first equation by -4:
-12x-4y=-7.00
2x+4y=2.00
===========
-10x=-5.00
x=.50
2(.50)+4y=2.00
1+4y=2.00
4y=1.00
y=.25
The chocolate bars costs 50 cents and the packs of gum costs 25 cents.
Check:
3(.50)+.25=1.75
1.50+.25=1.75
1.75=1.75
2(.50)+4(.25)=2.00
1.00+1.00=2.00
2.00=2.00
I hope this helps!
2007-03-18 05:29:34
·
answer #1
·
answered by Anonymous
·
4⤊
0⤋
Let x= cost of chocolate bar
Let y= cost of gum
3x+y=1.75 ;subtract 3x and isolate y: y=1.75-3x
2x+4y=2
Now, substitute y for y in the second equation
2x+4(1.75-3x)=2
2x+7-12x=2
-10x=-5
x=1/2 or 50 cents
Now plug in x for the other equation
3(1/2)+y=1.75
1.5+y=1.75
y=.25 or 25 cents
2007-03-18 12:09:40
·
answer #2
·
answered by J 2
·
1⤊
0⤋
The chocolate bars cost 50cent and the gum cost 25cent
2007-03-18 12:16:57
·
answer #3
·
answered by Anonymous
·
1⤊
0⤋
the chocolate bars are 50cents each and the gum is 25 cents
2007-03-18 12:06:41
·
answer #4
·
answered by jackie j 3
·
1⤊
0⤋
easy **** yo,
let x represent the chocolate bars and y represent the gum aight.
3x+y=1.75
2x+4y=2
now u have to eliminate one of the factors.
y would be the easiest; you multiply the first equation by -4
-12x-4y=-7
2x+4y=2 (remains the same)
now u got
-10x=-5
therefore x=-5/-10=0.5
now that u got x u sub it into either one of the equations
2(0.5)+4y=2
1+4y=2
4y=2-1
4y=1
y=1/4=0.25
so x=0.5 and y=0.25
2007-03-18 12:13:11
·
answer #5
·
answered by Anonymous
·
1⤊
0⤋
take the cost of a chocolate bar to be p and the cost of a pack of gum to be q.
therefore,
3p+q=1.75..........eq(i)
2p+4q=2.............eq(ii)
Multiplying eq(i) with 4 and subtracting it from eq(ii)
2p+4q=2
-(12p+4q=7)
you get
-10p= -5
10p=5
p=0.5
Putting the value of p in eq(i), we get
3*0.5+q=1.75
1.5+q=1.75
q=1.75-1.5
q=.25
So, the cost of a chocolate bar is 50 cents or $0.5, and the cost of a pack of gum is 25 cents or $0.25
2007-03-18 12:10:57
·
answer #6
·
answered by Bubblez 3
·
1⤊
0⤋